Undocumented migrants during the Covid-19 pandemic: social conditions, clinical features and pharmacological treatment - Gianfrancesco Fiorini; Antonello E. Rigamonti; Charilaos Galanopoulos; Martina Adamoli; Emanuela Ciriaco; Matteo Franchi; Eleonora Genovese; Giovanni Corrao; Silvano G. Cella (SAGE Publishing, 2020)
Population groups such as undocumented migrants have been almost completely forgotten during the COVID-19 pandemic, though they have been living in all European countries for decades and new arrivals have continued throughout the pandemic. The aim of this study was to investigate their health conditions during the current pandemic. We analysed the records of 272 patients with respiratory issues attending the outpatient clinic of a large charity in Milan, Italy: amongst them, 18 had COVID-19 confirmed by rhino-pharyngeal swab and 1 of them deceased. All the patients attending the clinic appeared to have several risk factors for COVID-19 and chronic conditions suspected to predispose to the disease and/or to worsen severity and outcomes: hypertension, immunosuppression and previous close contact with COVID-19 patients were the most important ones. Presenting symptoms were worse in patients with COVID-19 than in those with other respiratory issues. These results are discussed in light of the necessity to provide better healthcare to undocumented migrants.